2017
DOI: 10.1016/j.fitote.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial screening of Rumex species native to the Carpathian Basin and bioactivity-guided isolation of compounds from Rumex aquaticus

Abstract: Plants belonging to the genus Rumex (family Polygonaceae) are used worldwide in traditional medicine for the treatment of various diseases caused by different microorganisms (e.g. bacteria-related dermatologic conditions, dysentery and enteritis). The present study focused on the antibacterial screening of Rumex species native to the Carpathian Basin, and isolation of compounds from one of the most efficient species, Rumex aquaticus. The antibacterial effects of n-hexane, chloroform and aqueous fractions of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Naturally occurring anthraquinone compounds include physcion, emodin, aloe‐emodin, rhein and chrysophanol (1,8‐Dihydroxy‐3‐methyl‐9,10‐anthraquinone). Chrysophanol has anti‐inflammatory, neuroprotective, antibacterial, cardiac protective and anti‐depressant effects. In addition, it has shown strong anti‐neoplastic effects in breast cancer, non‐small cell lung cancer (NSCLC), and hepatocellular carcinoma (HCC) cells through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring anthraquinone compounds include physcion, emodin, aloe‐emodin, rhein and chrysophanol (1,8‐Dihydroxy‐3‐methyl‐9,10‐anthraquinone). Chrysophanol has anti‐inflammatory, neuroprotective, antibacterial, cardiac protective and anti‐depressant effects. In addition, it has shown strong anti‐neoplastic effects in breast cancer, non‐small cell lung cancer (NSCLC), and hepatocellular carcinoma (HCC) cells through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring anthraquinone compounds constitute a large family including physcion, emodin, aloe‐emodin, rhein, and chrysophanol (1,8‐dihydroxy‐3‐methyl‐9,10‐anthraquinone). A variety of pharmacological activities of chrysophanol such as anti‐inflammatory (Jeong et al, ; Wen et al, ), neuroprotective (Zhao et al, ; Zhao et al, ), antibacterial (Orban‐Gyapai et al, ), cardiac protective (Lian et al, ), and anti‐depressant (Zhang et al, ) activities have been reported. Interestingly, the anti‐neoplastic activities of chrysophanol have also been reported.…”
mentioning
confidence: 99%
“…The roots of docks are a rich source of anthraquinones and naphthalenes. Myddfai I recommends its use in treatment of pneumonia, which can be related to the antimicrobial properties of dock plants (Orbán-Gyapai et al, 2017). There is some certainty that the Welsh text is referring to R. conglomeratus in specific, due to the fact that species within the genus Rumex had unique Welsh names.…”
Section: Sharp Dock Rumex Conglomeratus Murray (Polygonaceae)-turthmentioning
confidence: 99%